Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12944-020-01421-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between the non-HDL-cholesterol to HDL-cholesterol ratio and non-alcoholic fatty liver disease in Chinese children and adolescents: a large single-center cross-sectional study

Abstract: Background The non-HDL-cholesterol to HDL-cholesterol (NHDLC/HDLC) ratio is closely related to a variety of dyslipidemia-related diseases. This study examined the relationship between the NHDLC/HDLC ratio and non-alcoholic fatty liver (NAFLD) in children and adolescents. Methods This cross-sectional survey included a total of 7759 eligible Chinese children and adolescents (5692 boys and 2067 girls) who received routine medical examinations. The anthropometric and laboratory data of the subjects were collected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…Regarding the association between UHR and ALT, Mehmet Ali Kosekli et al observed that UHR was positively associated with ALT through a controlled study (17). Moreover, a positive association between UHR and ALT was also reported in Chinese lean individuals by Ya-Nan Zhang et al (23). These results are consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the association between UHR and ALT, Mehmet Ali Kosekli et al observed that UHR was positively associated with ALT through a controlled study (17). Moreover, a positive association between UHR and ALT was also reported in Chinese lean individuals by Ya-Nan Zhang et al (23). These results are consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the association between IR surrogates and NAFLD can be partially explained by lipid parameters. 37 , 38 Dyslipidemia, a traditional NAFLD risk factor, is closely related to the onset of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhao et al [11] performed step-to-multiple logistic regression analysis on 1000 samples and obtained the NAFLD index (NFI), which includes ALT/ AST and TG, as a clinical scoring tool for predicting NAFLD. Accordingly, we compared the predictive value of UHR for NAFLD onset in non-obese adults to other indicators recently proposed in the literature [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%